2021
DOI: 10.1186/s12906-020-03187-w
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of autophagy through JAK2/STAT3 contributes to the therapeutic action of rhynchophylline on asthma

Abstract: Background Asthma is a chronic inflammatory disease characterized by airway remodeling and inflammation. Rhynchophylline is a kind of indole alkaloid isolated from Uncaria rhynchophylla. Here we investigated the effect of rhynchophylline on autophagy in asthma. Methods A mice model of asthma was established by ovalbumin challenge. Histopathological changes were assessed by hematoxylin-eosin staining, periodic acid-schiff staining and Masson stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Mice sensitized with OVA as the T celldependent antigen 41 have shown allergic airway inflammation that is dependent on Th2 responses in asthma. 42,43 Consistent with previous reports, 44,45 the expression levels of Beclin-1 and LC3-II increased in the lung tissues of the OVA-induced asthmatic group as compared to PBS mice (Figure S5B). As expected, TSLP neutralization in OVA-injected mice showed a significant reduction in these levels (p < .05, Figure S5B).…”
Section: Tslp Regulates Autophagy In a Murine Asthma Modelsupporting
confidence: 89%
“…Mice sensitized with OVA as the T celldependent antigen 41 have shown allergic airway inflammation that is dependent on Th2 responses in asthma. 42,43 Consistent with previous reports, 44,45 the expression levels of Beclin-1 and LC3-II increased in the lung tissues of the OVA-induced asthmatic group as compared to PBS mice (Figure S5B). As expected, TSLP neutralization in OVA-injected mice showed a significant reduction in these levels (p < .05, Figure S5B).…”
Section: Tslp Regulates Autophagy In a Murine Asthma Modelsupporting
confidence: 89%
“…This review has compiled the effects of Rhy with a particular focus on the CNS. However, Rhy impacts, among others, the cardiovascular and immune systems [ 3 , 10 , 84 , 297 ] (see also Section 2.1 and Section 2.7 ). Rhy was indeed shown to have antihypertensive roles via anti-sympathetic and vasodilatory effects that are mainly linked to ion channels [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Allergic asthma is linked with variable expiratory airflow and is characterized by the airway inflammation, bronchoconstriction, oxidative stress, collagen deposition, and mucus [ 4 ]. Our previous study has demonstrated that 40 mg/kg Rhy treatment by gavage protects murine airway against OVA-induced damages of allergic asthma by mitigating inflammation, airway remodeling, and oxidative stress [ 16 , 17 ]. In the current study, 20 mg/kg Rhy-SLNs or Rhy were subjected to OVA-induced mice to compare their therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Rhynchophylline (Rhy) is the major active ingredient of Uncaria rhynchophylla and possesses anti-inflammatory, vasodilatory, and anti-hypertensive functions [13][14][15]. In our previous study, we have found that Rhy markedly attenuates the allergic bronchial asthma, as evidenced by the alleviation of airway inflammation, airway remodeling, and oxidative stress [16]. The protective role of Rhy in asthma is mediated by repressing the smad and mitogen-activated protein kinase (MAPK) signaling transductions [17].…”
Section: Introductionmentioning
confidence: 99%